2019
DOI: 10.3389/fpls.2019.00312
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Methylation of T-DNAs Upon Agrobacterium Inoculation in Plant Leaves

Abstract: Agrobacterium tumefaciens has been foundational in the development of transgenic plants for both agricultural biotechnology and plant molecular research. However, the transformation efficiency and level of transgene expression obtained for any given construct can be highly variable. These inefficiencies often require screening of many lines to find one with consistent and heritable transgene expression. Transcriptional gene silencing is known to affect transgene expression, and is associated with DNA methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…Voucheret already in 1994 showed that transcriptional trans silencing could start quickly in developing seed, but complete inactivation might require few weeks [45]. After massive leaf infiltration with Agrobacterium, rapid methylation of T-DNA was detectable in the promoter region just 2–3 day post-infiltration and the levels continued to rapidly accumulate over the 1st week and then steadily up to 21 days [46]. In mitotically dividing cells, the maintenance methylation of newly synthesised DNA strands must be quick enough to ensure the replication of the epigenetic information between the two subsequent S-phases of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Voucheret already in 1994 showed that transcriptional trans silencing could start quickly in developing seed, but complete inactivation might require few weeks [45]. After massive leaf infiltration with Agrobacterium, rapid methylation of T-DNA was detectable in the promoter region just 2–3 day post-infiltration and the levels continued to rapidly accumulate over the 1st week and then steadily up to 21 days [46]. In mitotically dividing cells, the maintenance methylation of newly synthesised DNA strands must be quick enough to ensure the replication of the epigenetic information between the two subsequent S-phases of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Cloning of the correct gene family member and gene orientation was confirmed by Sanger sequencing at the Australian Genome Research Facility Ltd. A. tumefaciens (GV3101 pMP90) containing the constructs of interest (except TaGGP2 -D) were co-infiltrated with A. tumefaciens containing a P19 construct [88] to prevent post-transcriptional gene silencing into the younger leaves of 6-week-old N. benthamiana plants (LAB strain) grown in a plant growth room (16 h daylength, 24 °C) [89]. Infiltration conditions were conducted as previously described [90]. Infiltration with A. tumefaciens containing the P19 construct alone was used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…Relative expression assays were run using the Eco Real-Time PCR System (Illumina) and resulting data analyzed with the supplied Illumina Eco software. Final reaction volumes were 10 µL and are as described in Philips et al (2019), with primer sequences presented in ( Supplementary Table 1 ). All liquid handling steps were performed using an Eppendorf epMotion 5070 liquid handling robot.…”
Section: Methodsmentioning
confidence: 99%